Green Buildings and Sustainable Engineering Proceedings of GBSE 2018 - Drück, Harald; Pillai, Radhakrishna G.; Tharian, Manoj G.; Majeed, Aysha Zeneeb (Springer Transactions in Civil and Environmental Engineering, 2019)
This book comprises the proceedings of the International Conference on Green Buildings and Sustainable Engineering (GBSE 2018), which focused on the theme "Transforming our Built Environment through Innovation and Integration towards a Smart and Sustainable Future". The papers included address all aspects of green buildings and sustainability practices in civil engineering, and offer a valuable reference resource for researchers, practitioners, and policy makers. .